Insulinoma‐associated protein 1 is a prognostic biomarker in pulmonary high‐grade neuroendocrine carcinoma. Issue 2 (28th April 2020) - Minami, Kazuhiro; Jimbo, Naoe; Tanaka, Yugo; Ogawa, Hiroyuki; Hokka, Daisuke; Nishio, Wataru; Yoshimura, Masahiro; Itoh, Tomoo; Maniwa, Yoshimasa
Abstract: Backgrounds and Objectives: Recent studies have suggested that insulinoma‐associated protein 1 (INSM1) is a useful marker for pathological diagnosis of pulmonary neuroendocrine tumors. In the present study, we investigated the association between INSM1 expression and prognosis in patients with pulmonary high‐grade neuroendocrine carcinomas (HGNEC) and assessed the usefulness of INSM1 as a prognostic biomarker in these patients. Methods: Seventy‐five consecutive patients with HGNEC who underwent complete surgical resections from January 2000 to December 2018 were enrolled in this study. We classified these patients into two groups: the INSM1‐positive group (n = 59) and INSM1‐negative group (n = 16). We compared the clinicopathological characteristics, overall survival (OS), and recurrence‐free survival (RFS) between the groups. In addition, we performed univariate and multivariate analyses to identify the prognostic factors associated with postoperative survival. Results: Significant differences in tumor diameter and vascular invasion between the groups were found. OS and RFS were significantly poorer in the INSM1‐positive group than in the INSM1‐negative group. Univariate and multivariate analyses revealed that INSM1 expression was the strongest predictor of poor prognosis for OS and RFS. Conclusions: INSM1 expression had the greatest influence on the prognosis in patients with HGNEC and may be a prognostic biomarker in these patients.